Nomenclatural remarks on Cyanogaster Oken 1823 and Cyanogaster Blainville 1825 (Mollusca: Gastropoda: Pleurobranchaeidae) - Britz, Ralf; Mattox, George M. T.; Toledo-Piza, Monica; Marinho, Manoela M.f. (Zootaxa, 2013)
We recently published the description of a miniature fish species of the teleost order Characiformes from the Amazon basin in Brazil and named it Cyanogaster noctivaga (Mattox et al. 2013). Shortly after the description was published we received e-mails from several colleagues informing us that the genus name Cyanogaster Mattox et al. was preoccupied in Mollusca by Cyanogaster Oken 1823 and/or Cyanogaster Blainville 1825. We then checked the original publications and we found several interesting facts pertinent for the issue that we summarize here.